Experimental Investigation of Transient Liquid Phase Bonding of IN 718 Superalloy and Enhancement of Bond Quality - Tarai, Uttam Kumar (My University, 2023)
The present research work started with an objective to understand the fundamental kinetics of transient liquid phase (TLP) bonding of nickel-base superalloys; Inconel 718 (IN 718) and deliver methodologies for the improvement of bond properties. The role of process parameters in joining IN 718 with the TLP bonding process is explored with an aim to improve the mechanical properties of the bond. From the experimental investigation, it was ascertained that the bonding temperature, time, and interlayer type and size are the most important process parameter of the TLP bonding process. The higher bonding temperature, time, and optimal interlayer thickness improve the mechanical properties of the TLP bonded IN 718 joint. Higher bonding temperature reduces the isothermal solidification (IS) time. Inadequate bonding time leads to the formation of centreline eutectics in the TLP joint due to athermal solidification of the residual liquid remaining in the bond area. The IS time of the TLP bonding process depends upon factors like temperature, the diffusivity of the melting point depressants (MPD), and the width of the interlayer material. To obtain good bond properties, complete isothermal solidification is necessary. In order to determine IS time, the kinetics of TLP bonding should be known to the industries. To study the kinetics of the TLP bonding and to reduce the experimental time and cost, the interrupted differential scanning spectroscopy (DSC) method was used in the current investigation. The DSC method successfully described the kinetics of the TLP bonding. From the enthalpy of solidification of the DSC curve, the IS time of a material was obtained. And the results of the investigations are in good agreement with the experimental results of the other author.
Supervisors: Pal, Sukhomay, Robi, P S
Robi, P.S.
Keywords: Transient Liquid Phase Bonding; Inconel 718; Post-bond Heat Treatment; Isothermal Solidification; High- temperature Property; Mechanical Alloying; Homogenization Stage